Biossíntese de nanopartículas de prata com extrato de aveloz e seu efeito na conservação e fisiologia de morango - Oliveira, Shirlene Souza (2019)
Phytomolecules in Euphorbia tirucalli (hazel) extract can reduce silver ions to nanoparticles in a process called green synthesis. Silver nanoparticles (AgNPs) have efficient antimicrobial action against bacteria and fungi, but little has been studied about their application in agriculture, especially against postharvest phytopathogens, and this may be beneficial for the conservation and extension of shelf life of stored strawberries. The objective of this work was to perform green synthesis of AgNPs with hazelnut extract (Av), and to evaluate their effect on conservation and postharvest physiology of strawberries. In green synthesis silver nitrate (AgNO3) was reduced with Av to produce Av-AgNPs. The morphology and size of Av-AgNPs were analyzed by scanning electron microscope. The chemical composition was determined by Energy Dispersive X-ray Spectrometry, and percentage size dispersion was performed by laser diffraction. The in vitro antifungal activity of Av-AgNPs was tested against Botrytis cinerea and Rhizopus stolonifer. Total phenolic compounds and antioxidant activity of hazelnut extract and Av-AgNPs were analyzed. Strawberries were treated with Av-AgNPs (dipping) and stored (5 ° C) for 12 days. Respiratory rate, degradation index, fresh mass loss, firmness, color, total phenolic compounds and antioxidant activity of the fruits were evaluated. According to the results, the synthesis of Av-AgNPs was confirmed with maximum absorption at 449 nm and presented sizes between 40 and 90 nm. Av-AgNPs showed inhibition of B. cinerea growth, but were less effective for R. stolonifer. The total phenolic content and antioxidant activity of the Av-AgNPs solution were lower than the hazelnut plant extract. Total phenolic compounds, antioxidant activity, fresh weight loss, color and firmness of strawberries were not influenced by Av-AgNPs. Treated strawberries showed lower respiratory rate than control, and showed no signs of microbiological degradation until 9 days of storage. This study showed that the green synthesis of AgNPs with hazelnut extract produced nanoparticles smaller than 100 nm, and that Av-AgNPs were effective against microbiological degradation of strawberries during storage, which was decisive for their better conservation.